A systemic analysis of secondary school mathematics teachers' attitudes toward assessment of learning - Chafi, Chaimae; Chergui, Mohamed; El Wahbi, Bouazza (Intelektual Pustaka Media Utama, 2024)
Aware of the various issues involved in assessing learning, but also of the difficulties encountered in classroom practice of this pedagogical act, we set out in this article to explore and analyze the assessment practices of secondary school mathematics teachers and the conceptions they underlie. The study was conducted from a systemic perspective. We therefore targeted three aspects in our study: the conceptual, the institutional, and the docimological. Analysis of the attitudes declared by a random sample of mathematics teachers enabled us to confirm that pedagogical, and in particular cognitive, issues do not represent a priority for them in assessment practices. They focus more on the organizational aspect of examinations, with a remarkable lack of concern for docimological considerations to give credibility to the assessments carried out.